Identification of CFTR variants in Latino patients with cystic fibrosis from the Dominican Republic and Puerto Rico. Issue 2 (30th October 2019) - Zeiger, Andrew M.; McGarry, Meghan E.; Mak, Angel C. Y.; Medina, Vivian; Salazar, Sandra; Eng, Celeste; Liu, Amy K.; Oh, Sam S.; Nuckton, Thomas J.; Jain, Deepti; Blackwell, Thomas W.; Kang, Hyun Min; et al.
Abstract: Background: In cystic fibrosis (CF), the spectrum and frequency of CFTR variants differ by geography and race/ethnicity. CFTR variants in White patients are well‐described compared with Latino patients. No studies of CFTR variants have been done in patients with CF in the Dominican Republic or Puerto Rico. Methods: CFTR was sequenced in 61 Dominican Republican patients and 21 Puerto Rican patients with CF and greater than ​​​​60 mmol/L sweat chloride. The spectrum of CFTR variants was identified and the proportion of patients with 0, 1, or 2 CFTR variants identified was determined. The functional effects of identified CFTR variants were investigated using clinical annotation databases and computational prediction tools. Results: Our study found 10% of Dominican patients had two CFTR variants identified compared with 81% of Puerto Rican patients. No CFTR variants were identified in 69% of Dominican patients and 10% of Puerto Rican patients. In Dominican patients, there were 19 identified CFTR variants, accounting for 25 out of 122 disease alleles (20%). In Puerto Rican patients, there were 16 identified CFTR variants, accounting for 36 out of 42 disease alleles (86%) in Puerto Rican patients. Thirty CFTR variants were identified overall. The most frequent variants for Dominican patients were p.Phe508del and p.Ala559Thr and for Puerto Rican patients were p.Phe508del, p.Arg1066Cys, p.Arg334Trp, and p.I507del. Conclusions: In this first description of the CFTR variants in patients with CF from the Dominican Republic and Puerto Rico, there was a low detection rate of two CFTR variants after full sequencing with the majority of patients from the Dominican Republic without identified variants.